The choice of the Insurance Company for the Insurance bail tenant on the view of the brokers - Silva, Júlio César Bezerra da (Review of Business Management, 2007)
This research had the purpose of evaluating broker’s decisive process of the insurance bail tenant, seeking to know some aspects that influence the choice of this professional by a insurer to indicate to their customers. For that, it considered in a first moment the opinion of 10 (ten) of the largest brokers who operate in this segment in Brazil; the opinions were collected through interviews that generated several assertive about the subject. With the determination of these assertive, we developed a questionnaire applied to 112 brokers who operate with the insurance bail tenant in Brazil. This questionnaire sought to measure the brokers concordance with regard to the assertive collected in the first phase of this research. In the accomplished bibliographical research, we present a purchase insurances brokers behavior model, that we showed entirely related to assertive providing thus a better understanding concerning of the decisive process of these intermediary. With the interview, we could confirm the items importance related in the interview, and to conclude that the insurance bail Tenant broker nominates to their customers a insurer that besides providing them with larger profit and to bring more satisfaction to customers, it also recognizes him as important professional, provide working better terms, be more efficient in their operations and have better quality in his services. Key-words: Decisive process. Insurances broker. Insurance bail tenant. Insurance company choice.